Analisis Nine Steps of Strategic Public Relations Teater Pandora Melalui #MempermainkanRuang - Wattimena, Grace Heidy Jane Amanda; Agustin, Dorothea (Jurnal Pustaka Komunikasi, 2024)
#MempermainkanRuang is a Pandora Theater campaign initiated by the Jakarta Theater Community. The aim of this action is to increase public awareness about the limitations of theater buildings in Jakarta. Apart from that, to change the stigma of theater, which was previously considered boring and stiff. #PlayingWithSpace does not only mean space as a physical facility, but also acceptance, accessibility and opportunity, especially for young people. The presence of public relations in the world of creative industries is starting to be taken into account, so the aim of this research is to show the communication strategy of the #MakingSpace campaign from a public relations perspective. Apart from that, to see the obstacles that occur in implementing the campaign communication strategy. This research uses a qualitative descriptive method using Smith's Nine Steps of Strategic Public Relations communication strategy theory. The research results show that currently Pandora Theater uses social media Instagram and word of mouth communication techniques as the main communication strategies in outreach. Factors inhibiting implementation are benchmarking, the number of operational teams (human resources), communication strategy activation which only occurs every time there is a certain program and there are no simultaneous written reports.